(untitled) (Praxis Educativa, 2012)
During the course of the XX century an epistemological conception of research centered on theoretical contributions has prevailed in our country. For those who follow(ed) this trend, researchers create rules for action that, applied by teachers, can transform education, bringing about higher quality. In contrast to this perspective, the development of action research involves the analysis of the problems of the educational reality. Departing from a retrospective reflection on some kind of problem situation, practitioners of this trend elaborate a plan- prospective with respect to the action and retrospective in relation to the initial situation. Educational transformation is not conceived without the committed action of teachers via research. The present crisis calls for research, not as experts that observe the different educational problem areas from the outside, but as part of collaborative teams of teachers, that on the basis of reflection upon their own theories, will be able to develop plans of action for transformation and improvement.